Therapeutic alternatives for the treatment of ocular toxoplasmosis - Harley Da Silva Tavares, Gisele Rodrigues Da Silva (Journal of Applied Pharmaceutical Science, 2020)
Ocular toxoplasmosis is caused by Toxoplasma gondii, inducing retinochoroiditis. It is the leading cause of infectious posterior uveitis worldwide. Its treatment is based on oral drug administration. However, the blood–ocular barrier systems make the penetration of therapeutic drug concentrations within the eye difficult, limiting the effectiveness of treatments. In this context, ocular drug delivery systems represent therapeutic alternative for the treatment of ocular toxoplasmosis. In this study, a review of clinical manifestations, diagnosis, treatment, and perspectives regarding the treatment of ocular toxoplasmosis was conducted. A search was carried out on ScienceDirect, Scopus, Web of Science, PubMed, and SciELO, and the following keywords were used: toxoplasmosis, ocular toxoplasmosis, toxoplasmic retinochoroiditis, and congenital toxoplasmosis; and Boolean operators, associated with other keywords, such as epidemiology, ocular toxoplasmosis diagnosis, ocular toxoplasmosis treatment, and ocular toxoplasmosis perspectives, were applied. In conclusion, ocular toxoplasmosis still lacks effective treatment. Therefore, it is essential to develop new molecules and/or new drug delivery systems capable of releasing therapeutic doses of anti-Toxoplasma drugs directly in the posterior segment of the eye, for an extended period, since complications resulting from the disease may shorten the productive life of individuals and may even lead to blindness.
Keywords: Toxoplasmosis, ocular toxoplasmosis, toxoplasmic retinochoroiditis, ocular drug delivery systems, ocular implants.